Rotenone Modulates Caenorhabditis elegans Immunometabolism and Pathogen Susceptibility - Mello, Danielle F.; Bergemann, Christina M.; Fisher, Kinsey; Chitrakar, Rojin; Bijwadia, Shefali R.; Wang, Yang; Caldwell, Alexis; Baugh, Larry Ryan; Meyer, Joel N. (Frontiers in Immunology, 2022)
Mitochondria are central players in host immunometabolism as they function not only as metabolic hubs but also as signaling platforms regulating innate immunity. Environmental exposures to mitochondrial toxicants occur widely and are increasingly frequent. Exposures to these mitotoxicants may pose a serious threat to organismal health and the onset of diseases by disrupting immunometabolic pathways. In this study, we investigated whether the Complex I inhibitor rotenone could alter C. elegans immunometabolism and disease susceptibility. C. elegans embryos were exposed to rotenone (0.5 µM) or DMSO (0.125%) until they reached the L4 larval stage. Inhibition of mitochondrial respiration by rotenone and disruption of mitochondrial metabolism were evidenced by rotenone-induced detrimental effects on mitochondrial efficiency and nematode growth and development. Next, through transcriptomic analysis, we investigated if this specific but mild mitochondrial stress that we detected would lead to the modulation of immunometabolic pathways. We found 179 differentially expressed genes (DEG), which were mostly involved in detoxification, energy metabolism, and pathogen defense. Interestingly, among the down-regulated DEG, most of the known genes were involved in immune defense, and most of these were identified as commonly upregulated during P. aeruginosa infection. Furthermore, rotenone increased susceptibility to the pathogen Pseudomonas aeruginosa (PA14). However, it increased resistance to Salmonella enterica (SL1344). To shed light on potential mechanisms related to these divergent effects on pathogen resistance, we assessed the activation of the mitochondrial unfolded protein response (UPRmt), a well-known immunometabolic pathway in C. elegans which links mitochondria and immunity and provides resistance to pathogen infection. The UPRmt pathway was activated in rotenone-treated nematodes further exposed to the pathogenic bacteria P. aeruginosa and S. enterica or the common bacterial food source Escherichia coli (OP50). However, P. aeruginosa alone suppressed UPRmt activation and rotenone treatment rescued its activation only to the level of DMSO-exposed nematodes fed with E. coli. Module-weighted annotation bioinformatics analysis was also consistent with UPRmt activation in rotenone-exposed nematodes and may be involved in the increased resistance to S. enterica. Together, our results demonstrate that the mitotoxicant rotenone can disrupt C. elegans immunometabolism in ways protective against some pathogen species but sensitizing against others.